Generation of hybrids in broadly sympatric ducks ... - Campagna, Leonardo (Dryad, 2022)
Although rare, hybrids are more common in broadly sympatric waterfowl than in any other avian family; yet, the behavioral ecology explaining their generation has remained controversial. Leading hypotheses are forced interspecific copulations, mis-imprinting caused by mixed broods, and scarcity of conspecific mates. Using a large sample of hybrid ducks solicited from North American hunters we evaluated these hypotheses by genetically determining the mother and father species of F1 hybrids. Based on abundances in areas where their breeding ranges overlap, the frequency of hybrids varied greatly from expectations, with hybrids between species within recently derived clades being much more frequent than those between more divergent clades. Forced copulations, as measured by large phallus length asymmetries between parentals, strongly predicted the father species of most F1 hybrids. Thus, most Anas acuta x A. platyrhynchos (Northern Pintail x Mallard) F1s were sired by A. acuta, and most A. platyrhynchos x Mareca ... : ddRAD sequencing and Sanger sequencing of mtDNA genes. ...